Statewide Assessment of the Hepatitis C Virus Care Cascade for Incarcerated Persons in Vermont. (March 2023) - Hale, Andrew J.; Mathur, Shivani; Dejace, Jean; Lidofsky, Steven D.
Objectives: Incarcerated persons in the United States have a high burden of hepatitis C virus (HCV) infection. This study assessed the impact of a statewide effort in Vermont to treat HCV in this group. Methods: We performed a retrospective, observational cohort study of all HCV-infected persons who were imprisoned in Vermont during the 19-month study period (December 2018–June 2020). The cascade of care comprised opt-out HCV screening, full access to direct-acting antiviral treatment (without hepatic fibrosis-based treatment restrictions), HCV specialist involvement, and medication-assisted treatment for patients with opioid use disorder. The primary outcome was sustained virologic response at 12 weeks after treatment completion (SVR12). Results: The study included 217 HCV-infected patients; the median age was 35 years (range, 18-73 years), 89% were male, 76% had opioid use disorder, 67% had a psychiatric comorbidity, and 9% had cirrhosis. Of the 217 patients, 98% had a liver fibrosis assessment, 59% started direct-acting antiviral treatment, 55% completed direct-acting antiviral treatment, and 51% achieved documented SVR12. Of the 129 HCV-infected persons who started direct-acting antiviral treatment, 92% completed therapy and 86% achieved documented SVR12. Psychiatric comorbidity was not significantly associated with achieving SVR12 (odds ratio = 0.67; 95% CI, 0.27-1.65; P = .38), nor was receiving medication-assisted treatment for patients with opioid use disorder (odds ratio = 1.45; 95% CI, 0.62-2.56; P = .45). Conclusions: This study reports the highest SVR12 rate achieved in a state incarcerated population to date. HCV treatment in incarcerated populations is a practical and efficacious strategy that should serve a foundational role in HCV elimination.